Несравненная: [роман] / Михаил Щукин - Щукин Михаил (Сибириада. Собрание сочинений, 2013)
Экземпляры: абонемент (20161011) / Инвентарный номер: 45669 / Цена: 249.50 / Авт.знак: Щ 95 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)